PENGARUH METODE HYPNOTEACHING TERHADAP AKTIFITAS BELAJAR DAN DAMPAKNYA TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN AL-ISLAM DI SMP MUHAMMADIYAH 1 JEMBER - Bahar Agus Setiawan (Universitas Muhammadiyah Jember, 2018)
In this modern era, there has been a significant progress in instructional methods as a result of creativity and innovation, one of which is indicated in the development of hypnoteaching. Applying the structural equation modelling through path analysis, this study aims to investigate whether there is a significant influence of hypnoteaching on both learning activities and outcomes of al-Islam unit. The study was conducted at SMP Muhammadiyah 1 Jember with three hypotheses. The results of that data analysis show the chi-square value of 88.25, p-value of 0.44, and RMSEA of 0.021, indicating: 1. here is a significant effect of hypnoteaching on learning activities. 2. There is a significant effect of learning activities on student learning outcomes 3. There is not a statistically significant effect of hypnoteaching on student learning outcomes Based on these results, it may be concluded that hypnoteaching can increase student learning activities and impact on student learning outcomes. However, hypnoteaching cannot directly affect the improvement of student learning outcomes. Keywords: hypnoteaching, learning activities, learning outcomes